Perceived recovery as a predictor of physical activity participation after mild stroke. (July 2013) - Wolf, Timothy; Koster, Jessica
<x xml:space="preserve">Abstract</x> Purpose: The purpose of this study was to identify what acute care variables and/or perceived recovery factors could predict decreased participation in physical activities post-mild stroke. Methods: Secondary analysis of persons with mild stroke. Participants were split into two groups based on the percentage of high-demand leisure (HDL) activities retained on the Activity Card Sort (ACS) at 6 months post-stroke. Demographic variables, measures from the acute care setting (National Institutes of Health Stroke Scale (NIHSS), premorbid Barthel Index, and Modified Rankin Scale), and a perceived recovery measure collected at 6 months post-stroke (Stroke Impact Scale (SIS)) were analyzed between groups using independent samples t-tests and logistic regression. Results: There were no significant differences between groups on any of the demographic or acute care setting measures. Logistic regression indicated that only the overall perceived recovery (p = 0.05) and strength domain scores (p = 0.01) of the SIS were statistically significant factors for determining the percent of retained HDL activities following mild stroke. Conclusions: Clinicians must consider the clients' own perceived recovery level and other more subjective factors in determining what barriers are limiting their physical activity participation after stroke.